Phimosis - Are we on right track? - Aditya Arvind Manekar; Narahari Janjala; Subrat Kumar Sahoo; Bikasha Bihary Tripathy; Manoj Kumar Mohanty (Wolters Kluwer Medknow Publications, 2022)
Background: Phimosis, a common paediatric condition, is defined as the inability to retract the preputial skin behind the glans. Current practice shows there is some confusion among the paediatricians towards this common condition and in differentiating it from the more common physiological preputial adhesion; leading to frequent referrals to a paediatric surgeon or a general surgeon, which can be addressed by the parents and the child physicians themselves. Aim: To find out the awareness towards the management of phimosis among the paediatricians. Materials and Methods: A questionnaire on this topic was generated using 'Google Forms' and was circulated among junior and senior residents, faculty in various medical colleges and consultants in private practice all over India and their response was collected and analysed. Results: We received a total of 221 responses from all over India from paediatric medicine trainees and consultants. Among them, majority (48%) were senior residents. According to the survey participants, the most (46%) find inability to retract the prepuce as the major presenting complaint. A straight away reference to a paediatric surgeon was preferred by majority of paediatricians (62.9%), though most of them were aware of them were aware of physiological adhesions and conservative management (94.2%). There was a belief among 43% about counselling each and every patient presenting with phimosis for circumcision. Among the respondents, 60.2% advised ultrasound of kidneys, ureter, and bladder to their patients and believed that backpressure changes alter the management of the child. A urine routine examination was advised by 70.1% of participants, with 46.6% believing that the presence of urinary tract infection changes the management of phimosis. Waiting up to 1 year of age before going for surgery was advocated by 71.5%. A major proportion of respondents (76%) believed all cases of phimosis should be referred to a surgeon, only 58.8% would voluntarily follow them up. There is still a belief among 69.7% of participants that all cases of phimosis should be referred to a paediatric surgeon and only few of them, 5.4% feel referring only indicated cases. Conclusion: Physiological phimosis is a common condition which can be addressed by the paediatricians themselves. Awareness is to be increased among them, especially during the training period regarding the proper management of this common condition, avoiding unnecessary circumcisions.